Inhibitory effect of chloroform on fermentative hydrogen and methane production from lipid-extracted microalgae - Yun, Yeo-Myeong; Cho, Si-Kyung; Jung, Kyung-Won; Kim, Mi-Sun; Shin, Hang-Sik; Kim, Dong-Hoon (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
To improve the sustainability of microalgae as a bioenergy feedstock, lipid-extracted microalgae (LEM) are often further treated by anaerobic digestion (AD). However, the residual chloroform used for extracting lipids as a solvent could inhibit this process, an aspect that has not been studied to date. In this study, the inhibitory effect of chloroform on H-2 and CH4 production was investigated by performing batch tests. To prepare the feedstock, Chlorella vulgaris was ultrasonicated and the supernatant was discarded after centrifugation. In case of H-2 production, it was found that the H-2 yield fell to almost half that of the control (15.6 mL H-2/g CODadded) at 100 mg CHCl3/L. The reason for the decrease of the H-2 yield with the increase of chloroform level was due to the change of metabolites from acetate and butyrate to lactate via a non-hydrogenic reaction. In comparison with H-2 production, a much more severe inhibitory effect of chloroform on CH4 production was observed. The inhibitor concentration (IC30, 60, and 90) On H-2 production was 138, 319, and 622 mg CHCl3/L, respectively, while concentrations of 15, 37, and 86 mg CHCl3/L were obtained on CH4 production. When the chloroform concentration was >= 25 mg/L on CH4 production, more than 2 g COD/L of organic acids remained, resulting in a decrease of CH4 yield. These findings indicate that the residual chloroform in LEM should be seriously considered to prevent possible microbial inhibition when designing a process for additional energy recovery from microalgae via AD. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: SODIUM INHIBITION; BIOMASS; PRETREATMENT; BIODIESEL; BACTERIA; WASTE; FEEDSTOCKS; DIGESTION; TOLERANT; REACTOR